Effect of Curcuma longa on T lymphocytes in rats induced to prostate cancer - Condorhuamán Figueroa, Martin (2022)
Worldwide, prostate cancer is the second most diagnosed type of cancer in the male population, as well as the fifth leading cause of death. Therefore, it is necessary to look for alternatives for its prevention and treatment. Objective: to determine the effect of the pulverized rhizome of Curcuma longa on T lymphocytes in an animal model of prostate cancer. Methodology: It is an experimental study, 30 male rats Holtzman from 10 to 12 weeks of age were used, with an average weight of 200 to 250 g. Prostate cancer induction was performed by administration of testosterone, progesterone, and N-nitroso-N-methylurea (NMU) at doses of 100 mg/kg, 50 mg/kg, and 50 mg/kg, respectively. The pulverized rhizome of Curcuma longa was administered in aqueous solution at doses of 200, 400 and 600 mg/kg. Determination of CD4+ and CD8+ T cells was analyzed by BD FACSCalibur flow cytometry using FlowJo software. Results: Curcuma longa at different doses significantly improved the percentage of CD4+ and CD8+ T lymphocytes in the animals that received the treatments, increasing the population subgroups by 50 to 100%. Likewise, a better effect on the inhibition of tumor growth was presented at the dose of 600 mg/kg. Conclusion: an increase in T lymphocytes by Curcuma longa was evidenced at all the doses tested, presenting better results at the dose of 600 mg/kg.